I thought it would be difficult, but this is actually something I can do – experiences with Virtual Reality-based cognitive training in persons with TBI - Truls Johansen; Martin Matre; Sveinung Tornås; Marianne Løvstad; Jennie L. Ponsford; Alexander Olsen; Anne Lund (Annals of Medicine)
Introduction Virtual reality (VR) has been suggested as a promising technology for delivering cognitive training to persons with traumatic brain injury (TBI), as it can provide situations resembling everyday activities. Studies have demonstrated that persons with TBI manage utilizing VR in clinical settings; however, no studies have investigated VR use in home settings. The aim of this study was to explore how persons with TBI experience utilizing VR for rehabilitation at home and how they experience VR as cognitive training.Methods Individual qualitative interviews were conducted with ten persons with TBI, aged 18–65. Participants had experience using VR, as they were recruited from the intervention group in a randomized controlled trial investigating VR in cognitive training. The data were analyzed using thematic analysis.Results Participants highlighted the importance of creating new routines when fitting VR into everyday life. They addressed how being in a virtual world contributes to their motivation for cognitive training. Three themes were developed: ‘Fitting VR-training into everyday life’, ‘Navigating through change’ and ‘Being in two worlds at the same time’.Conclusion This study shows that participants experienced VR as motivating, engaging, and easy to use, regardless of prior experiences with VR. The participants demonstrated how they included VR in everyday life by creating new routines when they performed cognitive training. Therewere few reports of adverse events. However, some experienced that VR had a negative impact on their energy level. Participants described the importance of therapeutic involvement for individual tailoring of the intervention.